2021
DOI: 10.1159/000515102
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use during the COVID-19 Pandemic: Self-Reported Changes and Motives for Change

Abstract: <b><i>Background:</i></b> In Europe, the COVID-19 pandemic triggered a range of restrictive measures, which may have impacted alcohol consumption. <b><i>Objectives:</i></b> We explored perceived changes in alcohol consumption, their association with sociodemographic characteristics and past year alcohol consumption, and self-reported reasons for change after CO­VID-19 restrictions in Norway. <b><i>Method:</i></b> A web-based survey was sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 13 publications
11
40
1
1
Order By: Relevance
“…Consistent with our findings, most studies found that a majority of those reporting a change, had reduced their drinking [10,14,15,18,21,31,32]. Moreover, our finding that an increase in drinking more often was reported when initial consumption was high, corroborates previous findings [9,20,24].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our findings, most studies found that a majority of those reporting a change, had reduced their drinking [10,14,15,18,21,31,32]. Moreover, our finding that an increase in drinking more often was reported when initial consumption was high, corroborates previous findings [9,20,24].…”
Section: Discussionsupporting
confidence: 93%
“…Hence, the estimated increase in the dispersion of the distribution and the increase in the prevalence of heavy drinkers might in fact represent an underestimate. However, sales data and estimates of unrecorded consumption for Norway suggest a slight increase or no change in total alcohol consumption in the second quarter of 2020 (the first months of the pandemic) compared to the same period in 2019 [20], which corresponds quite well with our findings. Additionally, the ESAC survey seems to have reached heavier drinkers to a larger extent, since baseline consumption was slightly above the usual population average [22].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The long-term psychological consequences for the health of the general population could end up being as significant as those caused by the direct infectious consequences. Let us contribute together with information published in this issue [1][2][3][4][5] on education, early detection, and early intervention to counteract this and to improve mental health and the quality of life in this challenging time.…”
Section: Doi: 101159/000517138mentioning
confidence: 99%